The prognosis of MYC translocation positive diffuse large B‐cell lymphoma depends on the second hit. (30th March 2015) - Clipson, Alexandra; Barrans, Sharon; Zeng, Naiyan; Crouch, Simon; Grigoropoulos, Nicholas F; Liu, Hongxiang; Kocialkowski, Sylvia; Wang, Ming; Huang, Yuanxue; Worrillow, Lisa; Goodlad, John; Buxton, Jenny; et al.
Abstract A proportion of MYC translocation positive diffuse large B‐cell lymphomas (DLBCL) harbour a BCL2 and/or BCL6 translocation, known as double‐hit DLBCL, and are clinically aggressive. It is unknown whether there are other genetic abnormalities that cooperate with MYC translocation and form double‐hit DLBCL, and whether there is a difference in clinical outcome between the double‐hit DLBCL and those with an isolated MYC translocation. We investigated TP53 gene mutations along with BCL2 and BCL6 translocations in a total of 234 cases of DLBCL, including 81 with MYC translocation. TP53 mutations were investigated by PCR and sequencing, while BCL2 and BCL6 translocation was studied by interphase fluorescence in situ hybridization. The majority of MYC translocation positive DLBCLs (60/81 = 74%) had at least one additional genetic hit. In MYC translocation positive DLBCL treated by R‐CHOP (n = 67), TP53 mutation and BCL2, but not BCL6 translocation had an adverse effect on patient overall survival. In comparison with DLBCL with an isolated MYC translocation, cases with MYC/TP53 double‐hits had the worst overall survival, followed by those with MYC/BCL2 double‐hits. In MYC translocation negative DLBCL treated by R‐CHOP (n = 101), TP53 mutation, BCL2 and BCL6 translocation had no impact on patient survival. The prognosis of MYC translocation positive DLBCL critically depends on the second hit, with TP53 mutations and BCL2 translocation contributing to an adverse prognosis. It is pivotal to investigate both TP53 mutations and BCL2 translocations in MYC translocation positive DLBCL, and to distinguish double‐hit DLBCLs from those with an isolated MYC translocation.